ChemInform Abstract: Synthesis and Antimicrobial Activity of 2‐(Pyridine‐3‐yl)‐4H‐chromen‐4‐one Derivatives. Issue 27 (13th June 2013) - Chate, Asha V.; Ghotekar, Dattatraya S.; Bhagat, Sunil S.; Gill, Charansingh H.
Abstract The novel title compounds (II) are synthesized by a simple and environmentally friendly method.